Gastro-Retentive Floating Matrix Tablets of Cefpodoxime Proxetil - K. Sreenivasa Rao, Rakesh R. Vairagkar, Dattatreya B. Udgirkar, Praveen S. Patil, Karnakumar V. Biradar (Journal of Applied Pharmaceutical Science)
The present work aims at the development and evaluation of Floating matrix tablets of Cefpodoxime Proxetil were undertaken to prolong gastric residence time. A visible Spectrophotometric method has been employed for the estimation of Cefpodoxime Proxetil at 263 nm and Beer’s law is obeyed in the concentration range of 5-40 μg/ml. Total 7 formulations (B1-B7) were prepared using guargum with carbopol 934P was used in different concentrations. Fourier transform Infrared spectroscopy confirmed the absence of any drug/polymers/excipients interactions. The tablets were prepared by direct compression technique, using polymer such as hydroxy propyl methyl cellulose (HPMC K4M), guargum and carbopol 934P in different combinations with other standard excipients like sodium bicarbonate and lactose. Tablets were evaluated for physical characterization viz. hardness, friability, swelling index, floating capacity, thickness and weight variation. Further tablets were evaluated in-vitro drug release for 12 hr. The effect of polymer concentrations on buoyancy and drug release pattern was also studied. In-vitro drug release mechanism was evaluated by PCP V-3 software. Carbopol 934P had a negative effect on the floating properties also decreased the drug release. A lesser FLT and a prolonged floating duration could be achieved by varying the amount of effervescent and using different polymer concentrations. The entire matrix tablets showed significantly greater swelling index, exhibited controlled and prolonged drug release profiles and some floated over the dissolution medium for more than12 hr. The paddle speed affected the floating lag time and floating duration it had a negative effect on the floating properties. The optimized formulation followed the higuchi release model and showed non-fickian diffusion mechanism. It also showed no significant change in physical appearance, drug content, floatability or in-vitro dissolution pattern after storage at 45 oC at 75 % RH for three months.
Keywords: Cefpodoxime Proxetil, swelling index, floating capacity, Guargum,HPMC, Carbopol 934P